A2-type granitoids in anorogenic settings of Tusham Ring Complex: New concept, relevant to existence of the Malani Supercontinent - Kumar, Naresh; Kumar, Naveen (Journal of Himalayan Earth Sciences, 2020)
This contribution discusses A2-type (sub-type of A-type granitoids) magmatic rocks which were emplaced in confusing tectonic settings and identified with mixed crust-mantle geochemistry. The Tusham Ring Complex (TRC), in the northern part of the Trans-Aravalli Block (TAB), is characterized by volcano- plutonic association, and belongs to Neoproterozoic Malani Igneous Suite (MIS). The rock-types exposed in TRC include intrusions of grey granite, pink granite, grayish green granite, biotite granite and ring dykes, extrusions of rhyolite, quartz porphyry and tuff, and some meta-sedimentary rocks (quartzite, quartz-mica schist and schorl rock). Field studies, petrography and geochemistry propose that the magmatic rocks have close linkage with the Malani anorogenic felsic magmatism and are i.e. a part of the Neoproterozoic Malani Supercontinent. The magmatic evolution established a close association in space and time between the explosive acid lava and high-level granite that form distinct ring structure and radial dykes in NW Indian shield. Trace elements and their ratio suggest that these are formed in A2-type tectono-magmatic environment which is an interesting subject of debate among modern petrologist.